PENGARUH LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI SMAN 11 KOTA JAMBI - M. Joko Saputra; Zuhri Saputra Hutabarat (Universitas Batanghari Jambi, 2023)
This study aims to find out the school environment influences learning outcomes in the Economics Subject of Class XI Students at SMAN 11 Jambi City. This research is included in the associative class of causality. Classified as associative because this research is to find out whether or not there is a relationship between the variables being studied. Categorized as causality, because this study aims to determine whether the observed variables have a certain causal relationship as theoretically suspected. The results showed a significance value of less than 5% is obtained, so it can be concluded that the school environment (X) has an effect on learning outcomes (Y) at SMAN 11 Jambi City. This means that there is a linear relationship between the school environment (X) and learning outcomes (Y) at SMAN 11 Jambi City. Keywords : School Environment, Learning Outcomes